PREDICTING THE RISK OF DEVELOPMENT OF THREATENED PREMATURE BIRTH IN WOMEN WITH UROGENITAL SYSTEM INFECTIONS (International Journal of Scientific Pediatrics, 2023)
Abstract: Determination of serum levels of metalloproteinase-12 and cystatin C increases the reliability of diagnosing the threat of preterm birth in pregnant women with urinary tract infections to prevent the occurrence of preeclampsia. The purpose of the study is to develop an early diagnosis and risk prediction scale for developing the threat of preterm birth, taking into account the study of biochemical markers in women with genitourinary tract infections. Materials and methods of research. We examined 153 women of reproductive age, of which 128 were patients with threatened preterm birth, as well as 25 conditionally healthy women. The diagnosis of the threat of preterm birth was made on the basis of cervicometry - ultrasound measurement of the length of the cervix, and infection of the genitourinary system was determined using the complex use of diagnostic methods, such as ultrasound of the genitourinary system, urine analysis according to Nechiporenko, bacterial culture of vaginal discharge. And this, in turn, indicates , that an increase in serum values of metalloproteinase-12 and cystatin C allows us to recommend it as a biochemical marker of UPR in pregnant women, which occurs against the background of infections of the genitourinary system, and for correction, long-term use of uroseptics against the background of micronized progesterone is recommended. Results and discussions: it was found that in pregnant women, the main provoking factor for increasing the concentration of cystatin C is pathological changes in the renal structure. And depending on the severity of proteinuria, the level of cystatin C increases. There were no statistically significant differences in the level of metalloproteinase-12 in the blood of pregnant women with UPR without PE and the control group. An increase in the concentration of MMP-12 in the blood is associated with the severity of PE. Conclusions: It has been established that in pregnant women, an increase in the concentration of cystatin C is associated with pathological changes in the renal structure and, depending on the severity of leukocyturia and proteinuria, the level of cystatin C increases
Keywords: premature birth; urinary tract infections; biochemical markers